PENGEMBANGAN APLIKASI BELAJAR PEMBELAJARAN IPA DI SD BERBASIS HOTS DIMENSI METAKOGNITIF DENGAN PENDEKATAN TPACK - Muhamad Rosidin; A. Syachruroji; Nana Hendracipta (STKIP Melawi, 2023)
Abstract: Education in Indonesia has been disrupted by the COVID-19 virus pandemic which has caused learning to be carried out at home, and the government is trying to do its best in school policies, which eventually some schools have carried out online learning and offline learning with the imposition of restrictions. The policy eventually created new problems mainly due to the unpreparedness of schools to face online learning. The unpreparedness is caused by several factors, one of which is the ability of teachers to integrate technological and information advances into learning. The development of technology requires humans to have a high level of thinking ability, while the ability to think needs to be trained in the younger generation at the elementary school level. This study uses the RD (Resarch and development) method which aims to find out how the process of making learning applications, the feasibility of learning applications, student and teacher responses to metacognitive dimensions of HOTS-based learning applications with the TPACK approach. The metacognitive dimension HOTS-based learning application with the TPACK approach is an interactive learning media in the form of an android application that contains learning menus such as learning videos, LKPD, E-Books, online multiplayer quizzes, and learning implementation plans to provide an overview of the process of learning activities using learning applications. The learning application received a positive response from students and teachers with a percentage score of 91.04% of the 25 student respondents which means it belongs to the